Skull base reconstruction using in situ bone flap in patients with pituitary adenomas treated by endoscopic endonasal approach - Chen, Kaile; Dai, Kexiang; Liu, Zhiyuan; Liu, Jinlai; Yu, Kuo; Lu, Ailin; Zhao, Peng (Frontiers in Neurology, 2023)
Objective The objective of this study is to study the effect of in situ bone flap (ISBF) repositioning, a recently proposed rigid skull base reconstruction technique, on patients diagnosed with pituitary adenoma undergoing endoscopic endonasal approach (EEA). Method A retrospective analysis was conducted on 188 patients with pituitary adenomas who underwent EEA from February 2018 to September 2022. Patients were divided into the ISBF group and non-ISBF group, according to whether ISBF was used during skull base reconstruction. Results Of the 75 patients in the non-ISBF group, 6 had postoperative cerebrospinal fluid (CSF) leakage (8%), while only 1 of 113 patients in the ISBF group (0.8%) had postoperative CSF leakage, indicating that the incidence of postoperative CSF leakage in the ISBF group was significantly lower than that in the non-ISBF group (P = 0.033). In addition, we also found that the postoperative hospitalization days of patients in the ISBF group (5.34 ± 1.24) were significantly less than those in the non-ISBF group (6.83 ± 1.91, P = 0.015). Conclusion ISBF repositioning is a safe, effective, and convenient rigid skull base reconstruction method for patients with pituitary adenoma treated by EEA, which can significantly reduce the rate of postoperative CSF leakage and shorten postoperative hospital stays.